Displacement in Focus: Newsletter for the Fragile and Conflict-Affected Food Systems Area of Work (October Issue) - Carrillo, Lucia; Hollerich, Gillian; Kosec, Katrina (CGIAR System Organization, 2025)
Displacement has reached record highs, reshaping communities worldwide. As of 2024, close to 120 million people have been forcibly displaced worldwide and more than 300 million live outside their country of birth. These movements are driven by a complex mix of conflict, poverty, climate change, and economic shocks. As a result, one in seven people globally are now a migrant or refugee—an extraordinary figure that speaks to the urgency of understanding and addressing the forces that push people from their homes.